Letter from J. Griffin to Mary MacDonagh, Sister Francesca, regarding Jospeh MacDonagh in prison, - Griffin, J. (1920)
Letter from J. Griffin to Mary MacDonagh, Sister Francesca, regarding Joseph in Mountjoy prison. He informs Mary that Mr. O Hanlon met with Joseph on Saturday to make temporary arrangements for the business and that the business was going on as usual and that "the volume of work has not depreciated". J. Griffin also mentions that Joseph can receive food from outside friends but is not sure whether he will be deported or not.